2016
DOI: 10.1371/journal.pone.0167145
|View full text |Cite
|
Sign up to set email alerts
|

The RAS-Effector Interface: Isoform-Specific Differences in the Effector Binding Regions

Abstract: RAS effectors specifically interact with the GTP-bound form of RAS in response to extracellular signals and link them to downstream signaling pathways. The molecular nature of effector interaction by RAS is well-studied but yet still incompletely understood in a comprehensive and systematic way. Here, structure-function relationships in the interaction between different RAS proteins and various effectors were investigated in detail by combining our in vitro data with in silico data. Equilibrium dissociation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 115 publications
7
48
0
Order By: Relevance
“…The fact that elevated RAS-GTP levels observed upon treatment with MEK or PI3K inhibitors did not appear to activate PI3K signaling suggests an apparent preference toward MAPK pathway activation over that of the PI3K pathway. Interestingly, two reports have shown that RAS-GTP interacts with the RBD of the RAF kinases with orders of magnitude greater affinity versus that of the PI3Ks (Burd et al, 2014;Nakhaeizadeh et al, 2016). Hence, we hypothesize that elevated RAS-GTP levels result in greater association of RAS-GTP with RAF versus PI3K irrespective of whether that activation was mediated through MEK or PI3K inhibition.…”
Section: Discussionmentioning
confidence: 77%
“…The fact that elevated RAS-GTP levels observed upon treatment with MEK or PI3K inhibitors did not appear to activate PI3K signaling suggests an apparent preference toward MAPK pathway activation over that of the PI3K pathway. Interestingly, two reports have shown that RAS-GTP interacts with the RBD of the RAF kinases with orders of magnitude greater affinity versus that of the PI3Ks (Burd et al, 2014;Nakhaeizadeh et al, 2016). Hence, we hypothesize that elevated RAS-GTP levels result in greater association of RAS-GTP with RAF versus PI3K irrespective of whether that activation was mediated through MEK or PI3K inhibition.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the CRAF Ras binding domain (RBD) crystallized in complex with either HRAS or RAP1A, indicating that both interactions are sufficiently strong to yield co-crystal structures (5,6). This multi-specificity of Raf kinases relates to the conservation of the effector binding site and RBD at the atomic molecular level (7). Thus, reagents that interfere with the Ras/Raf interaction are likely to efficiently inhibit the activation of growth signals over a wide range of conditions.…”
mentioning
confidence: 99%
“…Other than these therapeutic strategies, progress has been made in generating alternative agents to inhibit KRAS onc -RAF interaction which is needed to stimulate RAS-dependent oncogenic signaling 40,76 . Thus, a better understanding of the detailed interactions of KRAS onc with RAS binding domains and RAS association domains of its downstream effectors provides alternative opportunities for the inhibition of intermolecular interactions 77,78 . Table 2 provides a summary of studies examining the direct inhibition of KRAS mutant from 1997 to 2017.…”
Section: Direct Inhibition Of Krasoncmentioning
confidence: 99%
“…Because of the unsuccessful EGFR targeted therapy for KRAS onc -dependent cancers and the difficulty associated with targeting KRAS onc directly, a great deal of effort has been applied to target downstream effector pathways. The specific interaction of RAS family proteins with downstream effectors regulates various cellular functions 3,77,96,97 . Constitutive activation of downstream effector pathways by oncogenic KRAS results in the uncontrolled growth, proliferation, and survival of cancer cells 98 .…”
Section: Rna Interferencementioning
confidence: 99%